2019
DOI: 10.1139/cjss-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of corn straw biochar on soil water infiltration and retention at tilled and compacted bulk densities in the Yellow River Delta

Abstract: During field application of biochar, the bulk density of tilled soil initially decreases and then increases over time, until reaching the initial level of compacted soil. This study evaluated the optimal biochar particle size for promotion of water infiltration and retention in a saline soil with various bulk densities after application. Corn straw biochar, pyrolyzed at 450 °C for 0.5 h, was prepared in different particle sizes (S1 ≤ 0.25 mm, S2 = 0.25–1 mm, and S3 = 1–2 mm) and separately mixed into the 0–30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Infiltration model. The impacts of γ-PGA and γ-PGA SAP on soil water infiltration were analyzed and depicted using the Kostiakov infiltration model, as well as Philip infiltration model, respectively [33].…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Infiltration model. The impacts of γ-PGA and γ-PGA SAP on soil water infiltration were analyzed and depicted using the Kostiakov infiltration model, as well as Philip infiltration model, respectively [33].…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Biochar nanoparticles increased the contact angle of the mixed layer, which might alter infiltration rates and induce preferential water flow (Rasa et al, 2018; Yi et al, 2015). Previous studies have shown that different biochar application amounts and particle size significantly decreased water infiltration (Sun et al, 2019). However, the biochar application rate in most studies was >1.0%, and the particle size was greater than millimetre level (Pu et al, 2019; Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Chen et al [34] found that commercially available biochar nanoparticles (NBC) not only affected the volume of soil pore by blocking space between soil particles, but it also reduces cumulative infiltration by 13.75%. Sun et al [35] also found that biochar application decreased water infiltration.…”
Section: Cumulative Infiltrationmentioning
confidence: 94%